Everything but the Car: The Carport as Social Space in Puerto Rican Domestic Architecture - Colom Braña, Gloria M. (Material Culture Review, 2021)
The carport, a nondescript functional space within a majority of Puerto Rican houses, often accommodates different social practices throughout the year. Daily household activities such as laundry and childcare often take place in the carport, but it is also a site for landmark events such as birthdays, social gatherings, and Christmas parties. Designed exclusively for car storage, the carport is often used for everything but the car. In order to understand how this space came to be repurposed, this article focuses on the history of the introduction of the car and carport in Puerto Rico. The transformation of a single-use space into an all-purpose space with distinct cultural signifiers happened soon after the spread of the carport. The history of the colonial relationship between the United States and Puerto Rico is tied to the story of changes to the North American house form, particularly the most utilitarian spaces within the domestic sphere. The carport reflects the dreams and illusions of upward mobility and how that came crashing down in a seemingly economic free fall that began roughly in 2007 and has continued spiraling out of control.